Typical Products and Seal of Origin (O’Higgins Region, Chile) [Productos Típicos y Sello de Origen (Región de O’Higgins, Chile)] - Lacoste, P (Universidad Austral de Chile, 2021)
In the wake of loss of profitability in rural areas and the need to generate new economic activities to prevent rural-out migration, the orange economy has proposed to enhance the value of heritage and culture as a tool for territorial socio-economic development. To move forward in this direction, this article analyzes the agri-food heritage of the O’Higgins Region (Chile) with the purpose of identifying those products with potential of development and their eventual valorization with Seals of Origin and Records of Origin. The article uses both qualitative and quantitative social science research methods to learn about typical products and public policies aimed at their valorization. The study also detects products of great cultural value and commercial viability produced by artisans, farmers, and cultural makers. Paradoxically, the article detects strong shortcomings in the organizations in charge of assessing them (CODELCO, Ministry of Cultures, “Artesanías de Chile” Foundation, Ministry of Foreign Affairs, among others) due to a lack of knowledge about heritage and deficient strategies for appraisal. © 2021, Universidad Austral de Chile. All rights reserved.